RANCANG BANGUN LINKED DATA SEBAGAI PROTOTYPE APLIKASI REPOSITORY KERISOLOGI - , Boby Ertanto, Dr. techn. Ahmad Ashari, M.I.Kom. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Keris is a typical traditional weapon from Indonesian culture that has been recognized by UNESCO (United Nations Educational Scientific and Cultural Organization) as Masterpiece of the Oral and Intangible Heritage of Humanity. Many museums in Indonesia also collect various kinds of keris, but information about keris is still quite difficult to be obtained, because many discussions about keris are generally written in book, or spreading through word of mouth, there were also some webs or blogs talking about some keris but the information data is unstructured and represented in hypertext form so it is difficult to reuse the data The method used in this research to build kerisiologi data is using the linked data model, where data are presented not only just from one source but from various relevant sources linked on kerisologi. In publishing the kerisiologi data as the linked data was conducted mapping to the existing data in database and data available from other sources by linking URI in any data has been determined. To represent each data and relation in mapping was established vocabularies that appropriate with kerisologi topic. In the mapping process was used D2RQ Mapping to implement mapping becomes the linked data form. The results of tests was performed to the kerisiologi linked data in addition to successfully publish the data as linked data was also capable of integrating a relevant data of kerisologi data from various linked data sources. Besides that the system can display data of kerisiologi linked data in web applications along with data has been linked to various sources. Keywords: Linked data, Kerisologi, metadata, RDF, D2R Server, D2RQ Mapping.